Analisis Ekonomi Tiga Genotipe Kumis Kucing di Tiga Agroekologi - Pribadi, Ekwasita Rini; Rostiana, Otih; SMD, Rosita (Pusat Penelitian dan Pengembangan Perkebunan, 2014)
Plant varieties can be released as superior varieties after adaptation trials/observation. Superiority of certain variety can be assessed through production, quality and bioactive compounds, which are supported by financial feasibility of its cultivation. To obtain high-yielding varieties of java tea, the adaptation of six genotypes have been tested at three different locations, for two planting seasons. The study was conducted in November 2011 to December 2013, at Cimanggu Research Installation (240 m asl) Bogor, Cicurug Research Installation (550 m asl), and Sukamulya Research Installation (350 m asl), Sukabumi, West Java. Â The three locations are production center of java tea. Â The trial was arranged in a randomized block design with six treatments (six genotype), repeated four times. Data were analyzed discriptively. The feasibility assessment of each genotype was measured through level of technical efficiency: the yield of fresh and dry herb/unit area, economic efficiency was measured based on (1) revenue/unit area, (2) the ratio of net income and gross income, allocative efficiency (price) based on the ratio of operating expenses and gross income. The results showed that genotype C indicated more superior in technical and economic feasibility than genotypic A and B at agroecology and social of Sukamulya. The potential fresh weight of herb was 2,243 kg, whereas dry weight was 690 kg, net income Rp.1,138,676,- B/C ratio 1.34, the proportion of residual income net of operating expenses 52.04% and allocative efficiency 74.62% per 1,000 m2, during two harvesting times.